2021
DOI: 10.3389/fimmu.2021.638694
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Encephalitis Virus Infected Human Monocyte-Derived Dendritic Cells Activate a Transcriptional Network Leading to an Antiviral Inflammatory Response

Abstract: A comprehensive understanding of the human immune response to virus infection is imperative for developing effective therapies, antivirals, and vaccines. Dendritic cells (DCs) are among the first cells to encounter the virus and are also key antigen-presenting cells that link the innate and adaptive immune system. In this study, we focus on the human immune response to the mosquito-borne Japanese encephalitis virus (JEV), which is the leading cause of virus-induced encephalitis in south-east Asia and has the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 58 publications
3
13
0
Order By: Relevance
“…Robust activation of GBPs in response to JEV infection at both the transcript and protein levels has been shown in our previous studies on human monocyte derived dendritic cells and mouse embryonic fibroblasts ( Chauhan et al., 2021 ; Sharma et al., 2021a ). Here, we found that GBP1 expression was markedly induced in human epithelial HeLa cells upon JEV infection, and interestingly GBP1 strongly colocalized with JEV-NS1 protein that marks the virus replication complex.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Robust activation of GBPs in response to JEV infection at both the transcript and protein levels has been shown in our previous studies on human monocyte derived dendritic cells and mouse embryonic fibroblasts ( Chauhan et al., 2021 ; Sharma et al., 2021a ). Here, we found that GBP1 expression was markedly induced in human epithelial HeLa cells upon JEV infection, and interestingly GBP1 strongly colocalized with JEV-NS1 protein that marks the virus replication complex.…”
Section: Discussionsupporting
confidence: 62%
“…A detailed understanding of the host-virus interaction is critical for the development of effective antivirals ( Turtle and Solomon, 2018 ; Sharma et al., 2021b ). While there are a few reports that have suggested the induction of various interferon-stimulated genes (ISGs) at both transcription and protein levels during JEV infection ( Yang et al., 2011 ; Zhang et al., 2013 ; Chauhan et al., 2021 ; Sharma et al., 2021a ), the finer details of the innate immune landscape during JEV infection remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The life cycle of JEV starts with the bite of a carrier mosquito, which releases virus particles that interact with receptors present on the surface of host cells, such as pericytes [ 98 ], fibroblasts [ 99 ], endothelial cells [ 100 102 ], dendritic cells [ 103 ], and myeloid cells [ 10 ], which are susceptible to JEV infection and are the primary sites of propagation of the virus. After replication in these cells, the newly assembled virion particles now migrate towards brain cells such as neuronal cells [ 104 ] and microglial cells [ 105 ] by using infected dendritic cells and T cells for their transport [ 98 ].…”
Section: Jev Life Cyclementioning
confidence: 99%
“…Recently, the C protein crystal structure was revealed and it was shown to have αhelixes 1-4 secondary structure, which closely resembles with the capsid protein of DENV, WNV, and ZIKV [21]. Each monomer of the JEV capsid protein consists of four helices: α1 (amino acid [29][30][31][32][33][34][35][36][37][38], α2 (amino acid 44-57), α3 (amino acid [63][64][65][66][67][68][69][70], and the longest α4 (amino acid , connected by short loops. The amino-terminal of α helix-1 forms closed and open confirmation by which it tends to be flexible and allows possible antivirals against this domain.…”
Section: Jev Structure and Its Genomementioning
confidence: 99%
“…The virus invades primarily innate immune cells in the skin like keratinocytes, Langerhans cells, fibroblasts, dermal dendritic cells and endothelial cells [35]. The dendritic cells are the primary target for JEV infection and potential the secretion of pro-inflammatory cytokines such as IL6, IL8, IL12 and TNF-α [36] and attracts other immune cells by which virus gets opportunity to enter the draining lymph nodes and secondary lymphoid organs like the spleen, followed by other peripheral tissues like the kidney, liver, heart, and lungs. The virus replicates in macrophages in tissues and monocytes in the blood [37].…”
Section: Jev Pathogenesismentioning
confidence: 99%